VERBAL VIOLENCE AND HATE SPEECH RELATED TO WOMEN'S ISSUES ON SOCIAL NETWORKS : "FACEBOOK COMMENTS AS AN EXAMPLE" - Mahmood, Ribar; Mohammed, Murad (Humanities Journal of University of Zakho, 2024)
This research endeavor seeks to examine instances of verbal aggression and hate speech within social networks pertaining to women’s concerns in Kurdistan Region. The primary objective is to comprehend the utilization of such aggressive language and hate speech among social media users, particularly on Facebook, in the context of women’s issues. The study employs a mixed methods approach, utilizing a combination of netnography methodology, critical discourse analysis techniques, and content analysis. Five prominent Facebook posts were selected as the sample, with 100 comments randomly extracted from each post using the ExportComments website. This study’s significance is rooted in its scholarly pursuit to gain insights into the prevalence of hostile and disparaging language employed by Facebook users discussing women’s topics. The findings underscore a substantial prevalence of verbal aggression and hate speech directed at women’s matters on the platform. Moreover, this study contributes to the scholarly understanding of the underlying patterns of the employing of harsh language and hate speech, drawing on relevant theoretical frameworks.